Exploring the catalytic influence of development finance institutions (DFIs) on South African venture capital (VC) - Hunter, Renée (Graduate School of Business (GSB), 2023)
Development finance institutions (DFIs) have various roles to play in capital markets. Specifically, the three theoretical principles according to which DFIs are supposed to operate are 1) Financial sustainability, 2) Additionality and 3) Catalytic influence. The latter principle means that DFIs are expected, through using the financial and non-financial interventions at their disposal, to influence the investment activities and decision-making of other (private) sector investors, to enter into new markets, change their view on investment risks, or focus on achieving particular types of impact with their investment. Among others, this influence is theoretically aimed at venture capital (VC) activities. This research investigates the extent to which DFIs engage with VC activities in South Africa, and the extent to which these engagements may lead to influencing these VC activities. The data is collected through semi-structured interviews with VC stakeholders with activities in South Africa, and a thematic analysis is employed to uncover common themes and insights. The findings show that DFIs engage with equity in VC funds' establishment and investment decisions, and with debt in VCs' value creation; and that general market support influences the frameworks adopted, and market approaches used in VC funds' strategies and investment strategies. These engagements are experienced in both negative (due to slow and bureaucratic processes, feelings of dependency and risks of crowding out) and positive ways (due to good collaborative practices, practical benefits of DFIs investing in VC funds, and the skills and experience contributed by DFIs). The themes around influence of DFI mechanisms on VC activities are as follows: DFI investments enable VC funds to come into existence; VC funds' parameters are influenced by DFI requirements; DFIs' interests in direct investments influences VCs' investment decisions; DFI frameworks are adopted by VCs; DFIs' market and impact perspectives inform VCs' perspectives; DFIs' due diligence informs VCs' investment decisions; and VC investees receive DFI technical assistance. Ultimately, the study concludes that DFIs have catalytic influence on VC activities only in some respects. Specifically, DFIs do have catalytic influence on VC activities through their equity investments, in that these activities inform and direct the focus areas, parameters and exclusions of VC investments. However, DFIs do not have catalytic influence on VC activities through their general market support, since VCs that are likely to engage with DFIs are already sufficiently aligned in terms of market and impact outlook. Based on the findings, and to ensure that DFIs are as impactful and catalytic as they can be, this research recommends that DFI activities focus on and specialise in those areas where they can have most catalytic influence. This means focusing on funding VC funds, rather than making direct investments into early-stage ventures. Moreover, DFIs would be advised to adapt their structures and processes to be more aligned with the operating realities of VC activities - specifically to be more nimble and less bureaucratic, allowing DFIs to meaningfully and productively contribute to a fast-moving part of the industry.